Comparative analysis of the clinical characteristics and outcomes of patients with Wilms tumor in the United Kingdom and Japan. Issue 10 (31st May 2021) - Nakata, Kayo; Williams, Richard; Kinoshita, Yoshiaki; Koshinaga, Tsugumichi; Moroz, Veronica; Al‐Saadi, Reem; Vujanic, Gordan; Oue, Takaharu; Pritchard‐Jones, Kathy
Abstract: Background: Wilms tumor (WT) demonstrates epidemiological differences by world region and ethnicity. To enhance understanding of these differences, we retrospectively analyzed clinical trial data sets from the UK and Japan over a 20‐year period. Procedure: We used data from three consecutive clinical trials in the UK and a single study in Japan that enrolled patients diagnosed during 1996‐2015, to compare clinical characteristics and outcomes between countries. Results: During 1996‐2015, 1395 patients in the UK and 537 in Japan were included. Japanese patients have a significantly younger median age at diagnosis than those in the UK (28 months vs 39 months). The proportion of patients with stage IV, large tumors, and anaplastic histology appears to be higher in the UK than in Japan (18% vs 11%, 62% vs 49%, 8% vs 3%, respectively). During 2005‐2015, 77 hospitals treated WT in Japan compared with only 20 hospitals in the UK. Five‐year overall survival of patients with WT was over 90% in both countries, but five‐year event‐free survival of patients with stage IV was significantly lower in Japan than in the UK (50.0% vs 76.2%, P  = 0.001). Conclusions: Differences in age of onset, tumor size at diagnosis, and histology may reflect differences in the genetic background of patients with WT between countries, but population‐based phenotype‐genotype data are lacking. The difference in survival probability for stage IV patients may be due to different diagnostic criteria or different treatment strategies. Prospective, international clinical studies including genomic analyses are needed to confirm these findings and improve clinical practice.